Scattering of edge-state electrons from a two-level atom located near the zigzag edge of a phosphorene nanoribbon. (1st April 2022) - Rafie, M.; Daeimohammad, M.; Soltani, M.; Ghanbari-Adivi, E.
Abstract: In this study, the general scattering theory based on the Lippmann–Schwinger equation, along with the Green function approach, is applied to investigate the scattering of the mobile electrons from a two-level atom located in a one-dimensional (1D) lattice. We have shown that there is a high similarity between this issue and the scattering of the edge-state electrons from a two-state atom located near the edge of a zigzag nanoribbon of phosphorene. The method is then generalized to the study of this latter case. In both cases, it is assumed that the electron interacts with the electric dipole of the atom and it is shown that the scattering process may lead to the excitation of the atom and change its initial state. For both cases, the elements of the transition matrix, the transmission and reflection coefficients, and the excitation probability of the scattering atom are analytically calculated and discussed. Highlights: Edge states in zigzag phosphorene nanoribbons were analyzed. The edge state of the zigzag nanoribbon can be viewed as a quasi-1D lattice. The probabilities in question are sensitive to the strength of the interaction between the atom and the electron. The probabilities in question are sensitive to the energy of the atomic levels. For some energies, the excitation probability of the atomic impurity is considerable.